“A Blessing and a Curse”: Challenges, Strategies, and Needs of International Graduates in the Midwest USA - Nguyen, Tam Ngoc Minh; Coetzer-Liversage, Anthony; Kenne, Deric R. (CV. Literasi Indonesia, 2025)
International graduate students are among the most vulnerable populations in university settings due to diverse academic, social, and mental health challenges. Despite this, few studies have examined how they navigate these difficulties. This study explored the mental health experiences and coping mechanisms of international graduate students at a large, research-intensive university in the Midwestern United States through a resilience-informed lens. Using a descriptive qualitative design, nine participants were recruited through purposive sampling, and semi-structured interviews were conducted and analyzed using thematic analysis. Three main themes emerged: (1) the ups and downs of stress, describing the fluctuating nature of students’ emotional well-being; (2) finding ways to thrive, highlighting diverse coping strategies and personal growth; and (3) the need for proactive services, emphasizing students’ calls for tailored institutional support. While existing services were acknowledged, participants identified gaps in culturally and contextually relevant resources. This study contributes to the growing body of knowledge on international students’ mental health, coping mechanisms, and service needs in higher education.